2016
DOI: 10.1186/s13046-015-0281-z
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-associated macrophages correlate with the clinicopathological features and poor outcomes via inducing epithelial to mesenchymal transition in oral squamous cell carcinoma

Abstract: BackgroundBoth tumor-associated macrophages (TAMs) and the epithelial to mesenchymal transition (EMT) of cancer cells play key roles in promoting tumor progression. However, whether TAMs could induce EMT in the progression of oral squamous cell carcinoma (OSCC) remains undefined.ResultsHere we detected the expression of macrophages markers CD68 and CD163, epithelial marker E-cadherin and mesenchymal marker vimentin in 127 OSCC patients by using semi-quantitative immunohistochemistry. CD68 and CD163 expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
115
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 155 publications
(130 citation statements)
references
References 32 publications
5
115
0
5
Order By: Relevance
“…Interestingly, we also found that the number of double positive in the stroma CD68+ CD163+, commonly identified as pro‐tumor macrophages, was negatively correlated with expression of HLA‐DP/DQ/DR on tumor cells (Spearman r = −0.45 and P < .0001). The median value of the number of CD68+ CD163+ cells was used to identify samples with high or low number of CD68+ CD163+ cells in the stromal compartment.…”
Section: Resultsmentioning
confidence: 64%
“…Interestingly, we also found that the number of double positive in the stroma CD68+ CD163+, commonly identified as pro‐tumor macrophages, was negatively correlated with expression of HLA‐DP/DQ/DR on tumor cells (Spearman r = −0.45 and P < .0001). The median value of the number of CD68+ CD163+ cells was used to identify samples with high or low number of CD68+ CD163+ cells in the stromal compartment.…”
Section: Resultsmentioning
confidence: 64%
“…In that study, high intratumoral CD163 expression was found to be correlated with E‐cadherin loss (Yan et al ., ). Global density of macrophages also relates to EMT features in non‐small‐cell lung cancer carcinoma (NSCLC) (Bonde et al ., ) or head and neck cancer (Hu et al ., ).…”
Section: Emt and The Cellular Actors Of Inflammationmentioning
confidence: 97%
“…High proportions of TAMs in oral cancer predicted poor clinical outcome (8), perhaps through TAM-induced cancer cell EMT (25), which would facilitate invasive growth and increase metastatic potential. Although we examined TAM density in disease recurrence and not patient survival, macrophage density at the infiltrative front was not prognostically significant.…”
Section: Stromal Cells (Red Arrows) At the Invasive Front Of Carcinmentioning
confidence: 99%